Foreign direct investment (FDI), added value and environmental-friendly practices in furniture manufacturing: the case of Malaysia and Vietnam - Ratnasingam, Jegatheswaran; Ioras, Florin (2009)
Malaysia as a low-cost wooden furniture production hub has attracted substantial foreign direct investment (FDI) over the last two decades. However, globalization of the worldwide furniture industry has increased the competitive pressure from newly emerging furniture-producing nations, especially Vietnam, which has displaced Malaysia as the largest exporter of furniture in the South East Asian region. Based on this state of facts a study was undertaken to analyze the FDI trends in the Malaysian furniture industry from 1986 to 2005, using secondary published data and questionnaire based survey. The results were compared against the characteristics of FDI in Vietnam. The results of the study point out that although Malaysia offered greater political stability, better infrastructure, amenities, industrial-relation practices, a more stable exchange rate and greater adoption of environmental-friendly practices; the lower production cost and favorable investment policy appear to be the strengths of Vietnam in attracting foreign direct investments. Therefore, Malaysian policy-makers need to formulate policies based on creativity and innovation that would pave the way for the manufacture of higher added-value products that would ensure the continued attractiveness of Malaysia as a furniture FDI destination.